2019
DOI: 10.1177/0021998319857111
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation for strain rate and temperature dependence of transverse tensile failure of unidirectional carbon fiber-reinforced plastics

Abstract: In the present study, strain-rate and temperature dependence of the transverse tensile failure mode of unidirectional heat-resistant carbon fiber-reinforced plastics is numerically simulated by finite element analyses. In the analyses, interface failure and matrix failure are represented by cohesive zone modeling and continuum damage mechanics, respectively. For the continuum damage mechanics, Christensen's failure criteria of multi-axial stress states for each strain rate are applied to the matrix properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…The snapshots of the deformation of the glass fiber/PP material system at the final strain of 100% under various strain rates are shown in Figure 15. It was reported that the transverse tensile failure mode of unidirectional CFRTCs changes from matrix failure-dominant mode to interface failure-dominant mode with an increase of applied strain rate [37,38]. Our simulation results obtained the same conclusion.…”
Section: Resultssupporting
confidence: 82%
“…The snapshots of the deformation of the glass fiber/PP material system at the final strain of 100% under various strain rates are shown in Figure 15. It was reported that the transverse tensile failure mode of unidirectional CFRTCs changes from matrix failure-dominant mode to interface failure-dominant mode with an increase of applied strain rate [37,38]. Our simulation results obtained the same conclusion.…”
Section: Resultssupporting
confidence: 82%
“…Maligno et al [ 15 ], Totry et al [ 16 , 17 ], Segurado and Llorca [ 18 ], and Vaughan and McCartney [ 19 , 20 ] also included the effect of thermal residual stress generated during the production process. The influence of strain rate is investigated by Sao et al [ 21 ] and Shafiei et al [ 22 ]. Arteiro et al [ 23 ] investigated the effect of neighboring plies on the damage development inside a central ply.…”
Section: Introductionmentioning
confidence: 99%
“…Arteiro et al [ 23 ] investigated the effect of neighboring plies on the damage development inside a central ply. Jordan et al [ 24 ], Sato et al [ 21 ], and Bai et al [ 25 ] included the effect of temperature on the macroscale behavior. This is done by including a temperature dependency in the constitutive equations of the matrix material.…”
Section: Introductionmentioning
confidence: 99%
“…A resume of literature reveals that the effect of temperature on the mechanical properties of carbon fiber/epoxy composite materials has been studied by various previous investigations. 1,[5][6][7]10,13,14,21,[25][26][27][28] The fundamental mechanical properties including tensile, compression, and shear tests have been experimentally investigated. Prior research indicates that the temperature sensitivity of carbon fiber/epoxy composite materials highly depends on the resin properties, reinforcement type, fiber distribution directions and performance of fiber-matrix interfaces.…”
Section: Introductionmentioning
confidence: 99%